Benefits of Adoption of IFRS in Indian Banking Industry: Perspective of Various Stakeholders: Implications and Analysis of IFRS Adoption in Indian Banking Industry (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The idea of accounting is starting to be essential in the banking industry of India. Because of the Globalisation there's should move hand in hand based on the brand new standards and regulations established for banking sector. In the present situation banks will also be coping with the international market so it is likewise essential to keep the profiles based on the International standards in India. Therefore there's should follow IFRS in Indian banking industry for more effective globalised future. In this particular newspaper, an effort is created revealing the end result of evaluation of collected information from officials of the selected banks. For analyzing the information, both easy and advance statistical tools was used. In several instances easy statistics as typical, percentage, weighted typical and mean score was put on.